THE NEW SOCIAL REALITY: ARTIFICIAL INTELLIGENCE AND THE NECESSITY OF ALIGNING NATIONAL LEGISLATION WITH SOCIETAL EVOLUTION - Lungeanu, Robert-Nicolae (International Journal of Legal and Social Order, 2025)
This paper aims to analyse the implications of the development and use of artificial intelligence from both legal and social perspectives, in a context where contemporary society is deeply shaped by digitalization. Beyond the undeniable benefits brought by this emerging technology, a critical reflection is required on how national legislation can—and must—adapt to new technological realities. The study raises a fundamental question: to what extent can technological evolution be pursued without compromising core human values? In this regard, the analysis emphasizes the imperative need for balanced regulation that ensures the protection of fundamental rights while also supporting responsible innovation.